Sixteen months at the gold diggings. - Woods, Daniel Bates, 1809-1892. (New York, Harper & brothers, 1851)
Daniel B. Woods of Philadelphia sailed to California in February 1849, crossing Mexico to San Blas, and arriving in San Francisco in June. Sixteen months at the gold diggings (1851) recounts those travels as well as his experiences as a prospector in the Northern Mines on the American River and at Hart's Bar and other camps in the Southern Mines before starting home in November, 1850. His book offers an exceptionally realistic picture of the drudgery of mining and the business side of miners' companies.
Also available in digital form on the Library of Congress Web site.
Keywords: California -- Gold discoveries; California -- Description and travel; Business -- California